Trypanocidal activity of free and nanoencapsulated curcumin on Trypanosoma evansi - Gressler L.T. (2015)
Copyright © Cambridge University Press 2014.This study aimed to evaluate in vitro and in vivo trypanocidal activity of free and nanoencapsulated curcumin against Trypanosoma evansi. In vitro efficacy of free curcumin (CURC) and curcumin-loaded in lipid-core nanocapsules (C-LNCs) was evaluated to verify their lethal effect on T. evansi. To perform the in vivo tests, T. evansi-infected animals were treated with CURC (10 and 100 mg kg-1, intraperitoneally [i.p.]) and C-LNCs (10 mg kg-1, i.p.) during 6 days, with the results showing that these treatments significantly attenuated the parasitaemia. Infected untreated rats showed protein peroxidation and an increase of nitrites/nitrates, whereas animals treated with curcumin showed a reduction on these variables. As a result, the activity of antioxidant enzymes (superoxide dismutase and catalase) differs between groups (P<0·05). Infected animals and treated with CURC exhibited a reduction in the levels of alanine aminotransferase and creatinine, when compared with the positive control group. The use of curcumin in vitro resulted in a better parasitaemia control, an antioxidant activity and a protective effect on liver and kidney functions of T. evansi-infected adult male Wistar rats.